Proteomics-driven diagnostics and pathological insights: investigating amyloidoses and plasma cell disorders with mass spectrometry - Netzel, Brian (My University, 2024)
Amyloidosis is characterized by the deposition of misfolded and insoluble proteins known as amyloid fibrils in tissues and organs. Associated with a series of human degenerative disorders, it is distinguished primarily by the identity of the misfolded protein and may manifest in either localized (single tissue/organ) or systemic forms. Light chain (AL) and transthyretin (ATTR) are common forms of amyloidosis that share organ tropism for fibril deposition (heart, kidney, nervous tissue). AL amyloidosis additionally belongs to the plasma cell disorders, which result from the abnormal multiplication of a single plasma cell clone that produces an excessive quantity of immunoglobulin (Ig). While cell proliferation causes the disease in associated disorders (monoclonal gammopathy (MG), multiple myeloma (MM)), AL is caused by insoluble Ig free light chain (FLC) deposition. Diagnosis for these disorders typically begins with serum protein electrophoresis, which identifies abnormal protein levels but lacks sensitivity, often delaying early diagnosis due to methodologic limitations. Confirmation and differential diagnosis of amyloid and plasma cell disorders require biopsy, with recurrent cases necessitating a similar diagnostic odyssey to exclude secondary disease. Additionally, when confirmed, current approved therapies for amyloidosis minimize amyloidogenic protein, but patients often continue to experience organ dysfunction, morbidity, and mortality due to previous or ongoing tissue damage from already deposited amyloid. In order to address the issues with differential diagnosis, monitoring and lack of treatments targeted for improving symptomatic progression in amyloid patients, we report a series of computational pipelines and associated investigations designed to improve the use of mass spectrometry to appropriately respond to amyloidosis, MM, and MG. A new mass spectrometric methodology and interpretive software was developed to measure Igs and their subunits, improving diagnosis and monitoring of AL, MM, and MG. Additionally, proteomic studies were performed to investigate the mechanisms affecting proteostasis in AL and ATTR with cardiac involvement, and additionally to characterize the associations between FLC gene family identity in AL and their associations with organ tropism, between involved tissues in individuals, and clonal persistence over time. The work described here advances our capability to diagnose, monitor, and improve treatment options in patients with amyloidosis and associated disorders.
University of Minnesota Ph.D. dissertation. 2024. Major: Biomedical Informatics and Computational Biology. Advisors: Surendra Dasari, Yuk Sham. 1 computer file (PDF); ix, 135 pages.